Communication and Media Education in an Era of Big Data - Venkatasawmy, Rama (Journal of Interdisciplinary Studies in Education, 2018)
Fundamental aspects of work carried out in the communication, media and creative industries are growingly being impacted upon by intense data-centric occurrences or Big data – which is constituted by vast amounts of information generated about and by social media users, instagrammers, tweeters, online retailers and service providers, shoppers, subscribers and netizens in general. Such information is categorized, scrutinized and processed so that substantial indications, extrapolations and inferences can be derived: and those subsequently influence investment decisions, production processes and output generation in the media, communication and creative industries (such as television, journalism, advertising and public relations). The quantifying and computing data-driven procedures associated with the collection, examination and depiction of Big Data bear explicit resonance in comprehending the intersection of communication, media and creative industries with technology and society. This resonance inevitably needs to be assimilated into the contemporary teaching of communication and media programs in higher education contexts. It has become vital for educators to ensure that contemporary communication and media students fully understand why and how large-scale datasets are collected, analyzed and interpreted so as to make sense of and to create value out of digital information. Big Data has now to be not simply addressed but fully incorporated into communication and media education, essentially to enable future generations of communication and media professionals to understand and apply Big Data in decision-making and when generating creative output. It is necessary to include Big Data in the teaching curriculum of communication and media programs because Big Data developments are already impacting strongly on the ways of knowing and of doing, as well as on the negotiation of value and on ethical considerations within the communication, media and creative industries.